MOTHER EARTH AND RELIGIONS - Manninezhath, Thomas (Journal of Dharma, 1993)
Nadu Gaddika is an impressive drama which successfully awakens in us a sense of concern and commitment to the mother earth. In the last part of this play the chieftain of the tribe is forcefully grabbed and questioned for all the ruthless actions executed on the earth and the injustices inflicted on its people. He is then coerced to ask pardon for the exploitation of and violence to the earth. The chieftain kissed the earth as a sign of contrition for exploiting earth for personal comfort and commercial gain. This symbolic gesture of the chieftain is the admission of sacredness of the land. The betrayal of this sacredness is sacreilegious and therefore to be atoned for.